2021
DOI: 10.3390/ijms22105323
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of CRIM1 on Endometrial Receptivity in Goat

Abstract: In domestic ruminants, endometrial receptivity is related to successful pregnancy and economic efficiency. Despite several molecules having been reported in the past regarding endometrial receptivity regulation, much regarding the mechanism of endometrial receptivity regulation remains unknown due to the complex nature of the trait. In this work, we demonstrated that the cysteine-rich transmembrane bone morphogenetic protein (BMP) regulator 1 (CRIM1) served as a novel regulator in the regulation of goat endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…They also demonstrated that Atg16L1 is necessary for proper decidualization and blastocyst implantation using mice with a hypomorphic allele of the Atg16L1 gene (causes a partial loss of function) [99]. In addition, cysteine-rich transmembrane BMP regulator 1 (CRIM1) functions as a regulator of endometrial receptivity at least in part by facilitating Atg7-dependent autophagy in the goat endometrium [100].…”
Section: Role Of Autophagy In Embryo Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that Atg16L1 is necessary for proper decidualization and blastocyst implantation using mice with a hypomorphic allele of the Atg16L1 gene (causes a partial loss of function) [99]. In addition, cysteine-rich transmembrane BMP regulator 1 (CRIM1) functions as a regulator of endometrial receptivity at least in part by facilitating Atg7-dependent autophagy in the goat endometrium [100].…”
Section: Role Of Autophagy In Embryo Implantationmentioning
confidence: 99%
“…Several studies have been conducted on the pharmacological or genetic abrogation of autophagy [98][99][100][101], and the role of autophagy in embryo implantation has been largely elucidated. However, the effects of autophagic activators on embryo implantation are not uniform, although the pathways of autophagy activation by these compounds are similar.…”
Section: Potential Involvement Of Autophagic Regulation On the Effect Of Natural Products As Embryo Implantation Enhancermentioning
confidence: 99%
“…After the unique nucleus shape of the PVs was determined, the posterior part of the suspected PVS was taken out for scanning electron microscopy (SEM) analysis. The SEM analysis was performed as reported in a previous study (35). Briefly, after fixation with 2.5% glutaraldehyde in phosphate buffer at 4°C overnight, the suspected PVS samples with rod-shaped nuclei were dehydrated in ethanol, and critical point-dried.…”
Section: Identification Of the Pvsmentioning
confidence: 99%
“…Virus packaging and cell transfection were performed as previously reported. 12,22 As reported previously, we also generated recombinant lentiviral vectors encoding GFP-LC3-RFP and GFP-LC3, which are fluorescent probes used to evaluate autophagic flux. Goat MAP1LC3B cDNA (GenBank accession number: XM_018061829.1) was used to generate these vectors.…”
Section: Cell Transfection and Fluorescence Measurementsmentioning
confidence: 99%
“…11 Our previous study demonstrated that autophagy is involved in regulating cell proliferation, cell adhesion, and PG secretion in goat endometrial epithelial cells during early pregnancy. 12 Rizzo et al demonstrated that the downregulation of autophagic flux induced by LPS was counteracted by pretreatment with baicalin in intestinal epithelial cells. 13 Activation of autophagy in brain microvascular endothelial cells maintained the integrity of the blood-brain barrier during early hypoxia-induced cerebrovascular impairment.…”
Section: Introductionmentioning
confidence: 99%